TCAD Calibration of High-Speed Si/SiGe HBTs in 55-nm BiCMOS. (18th August 2016) - VU, Van-Tuan; Celi, Didier; Zimmer, Thomas; Fregonese, Sebastien; Chevalier, Pascal
Abstract : This paper presents and discusses the challenges and solutions to calibrate the TCAD of high-speed DPSA-SEG Si/SiGe HBTs in 55-nm BiCMOS. The variation of the 1D doping profiles with the emitter width observed from EDX measurements has been addressed by TCAD simulation. Simplified base link formation by controlling the boron diffusion through polycrystalline / mono-crystalline interface in Sprocess simulation is a central step to capture a reasonable maximum oscillation frequency ( f MAX ). Finally all physical models including band-gap narrowing, saturation velocity, high-field mobility and SRH recombination, which impact the SiGe:C HBTs performance, are calibrated in Sdevice module of Synopsys ® .